Development of Curriculum Management Models in the Addiction Science Study Program - Erna Setiyaningrum; Ismet Basuki; Sri Setyowati (IJORER : International Journal of Recent Educational Research, 2022)
Drug abuse among students is a worrying problem that can threaten the survival of nation. This study carried tesearch design for the development of the Four D model is a model to develop learning devices. This method and model were chosen to develop addiction science education management that required to conduct feasibility, product validity, and trial. The development model based on curriculum management development referred to 4D development model, and referred to two quality requirements, namely valid and effective. This research objectives are to develop of curriculum management model for addiction science study program at IOHC INA Mojokerto, East Jawa, Indonesia. The quality of the Addiction Education Management Curriculum based on the final results had met the criteria "Very Good", so that it was appropriate to be applied and implemented as a product of developing curriculum management models in the addiction science study program at IOHC INA Mojokerto, East Java. The implication of this research is development of this curriculum is much needed to help nursing institutions to be more competent in the field of addiction science.